A literature review on the construction and application of management accounting reporting system in China - Qiqi, Zhang; Teruki, Neilson; Alwie, Aryaty; Taasim, Shairil Izwan (HRMARS, 2024)
With the ongoing advancement of modern enterprise management theory, the management accounting reporting system has increasingly garnered attention as a crucial element of the enterprise’s internal decision support framework. This paper first provides a summary of the management accounting reporting systems developed by Chinese enterprises from various perspectives. Subsequently, through an extensive review of the literature, the paper examines the practical application of these reporting systems across different industries and enterprises of varying sizes. The reviewed cases illustrate not only the beneficial impact of management accounting reporting systems on improving corporate decision-making efficiency and optimizing resource allocation but also the challenges and issues encountered during their implementation. Finally, the paper offers valuable insights and lessons for enterprises in the development and implementation of management accounting reporting systems.